2007
DOI: 10.1088/0741-3335/49/8/004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of low density coronal plasma in low current x-pinches

Abstract: Experiments were performed on an x-pinch using a pulsed power current generator capable of producing an 80 kA current with a rise time of 50 ns. Molybdenum wires with and without gold coating were employed to study the effect of high z coating on the low-density (<5 × 10 18 cm −3) coronal plasma dynamics. A comparison of images from XUV frames and optical probing shows that the low density coronal plasma from the wires initially converges at the mid-plane immediately above and below the cross-point. A central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…More recently, Mitchell et al (2000) studied the behavior of the coronal plasma on a 450 kA x-pinch, and showed that the low-density coronal plasma contributes to jet formation through optical and XUV framing images. Beg et al (2006) made similar observations with a 160 kA generator, and additional investigations into the effects of wire coatings on the low density corona were reported by Haas et al (2007). These studies focused on the plasma evolution between the electrodes where the wire ablation contributed to the zippered formation of the plasma structure.…”
supporting
confidence: 57%
“…More recently, Mitchell et al (2000) studied the behavior of the coronal plasma on a 450 kA x-pinch, and showed that the low-density coronal plasma contributes to jet formation through optical and XUV framing images. Beg et al (2006) made similar observations with a 160 kA generator, and additional investigations into the effects of wire coatings on the low density corona were reported by Haas et al (2007). These studies focused on the plasma evolution between the electrodes where the wire ablation contributed to the zippered formation of the plasma structure.…”
supporting
confidence: 57%
“…This shunt of current effectively stops the expansion of the dense wire core at an earlier time in Ni than in Cu, and the core and corona sizes are significantly smaller as a result. Previous experiments with Ni also demonstrated that the ablated plasma in Ni convects a considerable fraction of the drive current to the axis [26], and other research works using two-wire X-pinches suggested that the ablation flaring from lower Z wires carry current to the axis more markedly than higher Z wires [27]. Nickel's modulation wavelength and coronal plasma behave as expected from an element heavier than Cu, while the transmission of current in its ablation flaring is characteristic of a lighter element.…”
Section: Discussion and Summarymentioning
confidence: 90%
“…Pulsed power plasma devices loaded as Zpinch, x-pinch, wire arrays or liners, have the ability to reproduce a vast variety of plasmas, among others dense plasmas for fusion studies, laboratory astrophysics plasmas, dense and hot point source plasmas for hard x-ray generation and lower density hot plasmas. Such plasma production is essential for basic plasma physics studies like for instance plasma instabilities generation but also for important plasma applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%